Traditional knowledge in weathering effects of climate variability on upland farming among Buhid Farmers in Occidental Mindoro, Philippines - Susanita G. Lumbo (Hasanuddin University, 2018)
This exploratory study highlights the tradidional knowledge employed by Buhid farmers in weathering effects of climate variability on upland farming. A total of 100 farmers from two Buhid settlements participated in the study. They are either young or middled-aged and with small or big households. Less than half of them are affiliated to community organizations. Majority have neither attended relevant trainings and seminars nor have been involved in community initiatives relating to climate variability adaptation. The farmers attribute poor soil, low yield, poor yield quality, water scarcity, depletion of natural resources, and crop pest and diseases as manifest effects of climate variability. They practice rituals, ecological farming, and food substitutes to counter negative effects of climate variability on upland farming. The Buhids’ organizational affiliation, trainings and seminars attended, and community involvement were found associated to the traditional knowledge employed in adapting to effects of climate variability on upland farming.